Effect of adult feeding on progeny production and sex ratio of Dinarmus basalis (Rond.) (Hymenoptera: Pteromalidae) - Haque, MJ; Islam, W (Journal of Bio-Science, 2012)
Context: Dinarmus basalis (Rond.) is a larval-pupal ectoparasitoid of the pulse beetles, Callosobruchus (Coleoptera: Bruchidae). This parasitoid could be used in suppressing the pulse beetle populations in stored conditions. Objective: To observe the influence of different food supplements on the progeny production and sex ratio of D. basalis when exposed to the pulse beetles separately. Materials and Methods: Mated females of D. basalis were introduced into separate Petri dishes (9.5 cm diam) containing 50 mature mung seeds infested with C. chinensis and C. maculatus. The parasitoids were provided with host and honey, host and sugarcane, host and egg yolk, host and yeast and host and agar, and host without food individually. After 24 h, the parasitized larvae with seeds were changed and the female parasitoids were provided with foods daily until adults died. After emergence total number of hosts and parasitoids were counted. The sex ratio of D. basalis were also calculated and their chi-squared tests were made. Results: The mean number of progeny production of D. basalis on C. maculatus-infested blackgram was significantly greater than those reared on C. chinensis-infested mug in all food regimes (Table 1). The progeny production on two host beetles differed significantly in relation to different foods (F= 4.85, P<0.01. C. chinensis; F= 38.34, P<0.01, C. maculatus). The most effective food supplement was honey, which enhanced offspring production of D. basalis on both the hosts, and egg yolk was the least effective. The percentage of progeny was more or less female-biased in all the treatments except the control. Conclusion: Food supplementation of D. basalis will significantly increase the efficiency of the parasitoid against storage pests including the pulse beetles. DOI: http://dx.doi.org/10.3329/jbs.v19i0.13004 J. bio-sci. 19 77-80, 2011